The 6-kilodalton peptide 1 of the family Potyviridae: small in size but powerful in function - Yu, Liansheng; Korxeelor, Xayvangye; Wang, Ziyi; Chang, Shuaifang; Jiang, Xue; Wu, Xiaoyun; Cheng, Xiaofei (Frontiers in Microbiology, 2025)
The Potyviridae family is one of the most economically significant groups of plant RNA viruses, causing severe yield losses in agriculturally important crops. Among the viral proteins encoded by potyviruses, the 6-kilodalton peptide 1 (6K1) has emerged as a critical, albeit poorly understood player in viral pathogenesis. Despite its small size, 6K1 exhibits diverse functions, including facilitating the assembly of viral replication complex (VRC), altering host membrane permeability as a viroporin, and interacting with host factors to promote infection. This review synthesizes current knowledge on 6K1, focusing on its structural characteristics, evolutionary conservation, molecular interactions, and potential as a target for antiviral strategies. We further discuss unresolved questions surrounding its putative ion channel activity, polyprotein processing dynamics, and functional parallels with animal virus viroporins. Understanding 6K1’s multifunctionality provides new insights into viral infection mechanisms and opens avenues for novel disease control approaches.